Case Report: Lateral C1–C2 puncture for intrathecal baclofen therapy: an alternative effective and safe approach after spinal cord injury - Rayan Fawaz; Rayan Fawaz; Rayan Fawaz; Hayat Belaid; Baptiste Eklu; Jean Baptiste Thiebaut; Manon Duraffourg; Manon Duraffourg (Frontiers in Pain Research)
Spasticity is a neurological disorder that disrupts the regulation of muscle tone following an injury to the central nervous system, such as spinal cord injury. Baclofen is the most effective medication for treating spasticity and can be delivered via a pump connected to an intrathecal catheter. The catheter is typically inserted via a lumbar punction and advanced up to the level corresponding to the disturbing spasticity. But this may not be possible, especially when cervical level is involved. We present the case of a patient with severe spasticity after a traumatic cervical spinal cord injury who successfully underwent a lateral C1–2 puncture for placement of a retrograde catheter to the C4 level, after an unsuccessful attempt at catheter placement via a lumbar puncture. The patient experienced a significant reduction in spasticity with no reported worsening during the 8 months follow-up period. The catheter placement via a lateral C1–2 puncture guided by innovative imagery with 3D reconstruction, may serve as an effective and safe alternative to deliver baclofen at the cervical level. Relevance of cervical ITB is discussed and issues involved are considered. The mechanism of action of ITB at cervical level, which is far from fully clarified, is crucial to reach the best clinical outcome and avoid si de effects and complications. Few clinical cases were published; hence the importance to present this case.